Sistem Otentifikasi Sidik Jari menggunakan Metode Minutiae Macthing berbasis Average Euclidean Distance - Himawan, Hendri (ReTII, 2019)
The fingerprint-based biometric system is one of the safety standard in office and used to check employee attendancee. The method that commonly used in fingerprints detection, is image extraction from fingerprint sensor acquisition. The image extraction will produce a special feature which is called minutiae. Each person has a specific minutiae that can be used as a basis for fingerprint detection. First step regarding to fingerprint detection is to convert the image into binary thus thinning image method can be implemeted to obtain skeleton image. After image thinning is applied, extraction minutiae is following by ridge bifurcation and ridge ending identification on the image. This research merely uses two types of minutiae. The next step in the extraction feature is image matching to test the similarity between the image from the data test and database. Euclidean distance is used to test the similarity both of images and thresholding method is to determine the degree of similarity. This study enhances the method by adding average Euclidean distance formulation, which considers the value from all similar fingerprints database. In order to test the result of the proposed method, the DB1 international standard data set are used which consist of 80 types of fingerprints from 10 different people. The result shows that the method applied has an accuracy of 81.25% which means that the method can be used as an algorithm to solve fingerprint detection problem..